2016
DOI: 10.1093/chromsci/bmw111
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework [Cd(LTP) 2 ] n for Improved Enantioseparations on a Chiral Cyclodextrin Stationary Phase in GC

Abstract: Metal-organic frameworks (MOFs) are a class of novel porous materials consisting of clusters or chains of metal ions and organic linkers. The chiral MOF [Cd(LTP)] (LTP = l(-)-thiazolidine-4-carboxylic acid) possesses infinite extension three-dimensional supramolecular reticular structure with right-handed helix. In this work, three capillary columns (A, B and C) containing MOF [Cd(LTP)], permethylated β-cyclodextrin (CD) and sodium chloride, and MOF [Cd(LTP)] and permethylated β-CD, respectively, have been pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…The thio and amino functional groups of the tpro − ligand can also participate in hydrogen bonding interactions, thus increasing the dimensions of the target products. However, such tpro-based complexes are still rare as of this writing [56,57,58,59]. A chiral l -thioproline species was employed as a ligand to react with the Zn(II) ions under mild conditions, in order to permit some labile compounds with coordinated water molecules to be produced.…”
Section: Resultsmentioning
confidence: 99%
“…The thio and amino functional groups of the tpro − ligand can also participate in hydrogen bonding interactions, thus increasing the dimensions of the target products. However, such tpro-based complexes are still rare as of this writing [56,57,58,59]. A chiral l -thioproline species was employed as a ligand to react with the Zn(II) ions under mild conditions, in order to permit some labile compounds with coordinated water molecules to be produced.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the incorporated MOF [Cd (LTP) 2 ] n improved the separations of 14 racemates: (±)-limonene, (±)-1-cyclohexyl amine, (±)-menthol, (±)-dihydrocarvyl acetate, (±)-2-hexanol, (±)-citronellal, (±)-1 phenylethylamine, (±)-rose oxide, (±)-2-amino-1-butanol, (±)-1-phenylethanol, (±)-2-phenyl-1-propanol, (±)-2-methyl-1-butanol, DL-alanine, and DL-arginine, on a permethylated β-CD stationary phase with good efficiency and reproducibility in gas chromatography. 149 A mixedmatrix membrane (MMMs) made of CD-MOF as a chiral selector and polyethersulfone as a matrix elucidated nearly 100% enantioselectivity of R-(+)-1-phenylethanol over S-(À)-1-phenylethanol with n-hexane, whereas the membrane enantioselectivity decreased with the permeation time in the case of methanol and ethanol. 143 The MMM showed a high permeation rate for R-(+)-1-phenylethanol, whereas, in a flux versus time graph, the flux approached zero when a nonpolar solvent n-hexane was used.…”
Section: Cd-based Mofsmentioning
confidence: 99%
“…The thio and amino functional groups of the tpro  ligand can participate in hydrogen bonding interactions to increase the dimensions of the target products. However, such tpro-based complexes were still rare as of this writing [56][57][58][59]. A chiral L-thioproline species was employed as a ligand to react with the Zn(II) ions under the mild conditions, so that it would permit some labile compounds with coordinated water molecules to be obtained.…”
Section: Syntheses Of Compounds 13mentioning
confidence: 99%